2000
DOI: 10.4049/jimmunol.165.12.6783
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Th1 and CD8+ Type 1 Cytotoxic T Cells Both Play a Crucial Role in the Full Development of Contact Hypersensitivity

Abstract: The role of CD4+ vs CD8+ T cells in contact hypersensitivity (CHS) remains controversial. In this study, we used gene knockout (KO) mice deficient in CD4+ or CD8+ T cells to directly address this issue. Mice lacking either CD4+ or CD8+ T cells demonstrated depressed CHS responses to dinitrofluorobenzene and oxazolone compared with wild-type C57BL/6 mice. The depression of CHS was more significant in CD8 KO mice than in CD4 KO mice. Furthermore, in vivo depletion of either CD8+ T cells from CD4 KO mice or CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
176
1
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(187 citation statements)
references
References 51 publications
6
176
1
4
Order By: Relevance
“…There have been major controversies on the respective roles of CD4 ϩ and CD8 ϩ T cells in the development of CHS inflammatory reactions (12). However, it has become clear that both CD4 ϩ and CD8 ϩ T cells can act as effector cells in this context (17). Wang et al (17) showed that both CD4 ϩ Th1 and CD8 ϩ Tc1 cells are crucial effectors in the CHS response to DNFB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been major controversies on the respective roles of CD4 ϩ and CD8 ϩ T cells in the development of CHS inflammatory reactions (12). However, it has become clear that both CD4 ϩ and CD8 ϩ T cells can act as effector cells in this context (17). Wang et al (17) showed that both CD4 ϩ Th1 and CD8 ϩ Tc1 cells are crucial effectors in the CHS response to DNFB.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become clear that both CD4 ϩ and CD8 ϩ T cells can act as effector cells in this context (17). Wang et al (17) showed that both CD4 ϩ Th1 and CD8 ϩ Tc1 cells are crucial effectors in the CHS response to DNFB. Previous studies have also demonstrated that cytokines play important effector and regulatory roles in CHS responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this rather polarized model is attractive, there may in practice be a requirement for both CD4 π and CD8 π T lymphocytes for the initiation and maintenance of a complete immune response to skin sensitizing chemicals. Certainly this is the implication from the results of recent studies performed in mice by Wang et al (30). On the basis of secondary depletion experiments from CD4 and CD8 knockout animals, they concluded both CD4 π Th1 cells and CD8 π Tc1 cells are required for the full development of contact hypersensitivity (30).…”
Section: Cd8 π Effector Cells and Interplay With Cd4 π Cellsmentioning
confidence: 99%
“…Certainly this is the implication from the results of recent studies performed in mice by Wang et al (30). On the basis of secondary depletion experiments from CD4 and CD8 knockout animals, they concluded both CD4 π Th1 cells and CD8 π Tc1 cells are required for the full development of contact hypersensitivity (30). This is despite the fact that in some cases it appears possible to generate CD8 π T lymphocyte responses to skin sensitizing chemicals in the absence of antigen-activated CD4 π cells (28,31).…”
Section: Cd8 π Effector Cells and Interplay With Cd4 π Cellsmentioning
confidence: 99%